Tracking Long-Lived Free Radicals in Dandelion Caused by Air Pollution Using Electron Paramagnetic Resonance Spectroscopy - Ireneusz Stefaniuk; Bogumił Cieniek; Agata Ćwik; Katarzyna Kluska; Idalia Kasprzyk (Molecules)
Studies on particulate air pollution indicate that a new type of pollutant should be considered from mainly fossil fuel combustion and automobile exhaust emissions, i.e., environmentally persistent free radicals. These radicals, ubiquitous in the environment, have a long life span and are capable of producing harmful reactive oxygen species. Samples of dandelion were collected in 2020 and 2021 in spring and late summer. Roots, leaves, flower stalks, and inflorescences of Taraxacum sp. were collected from six sites with three plants each, along with monitoring of particulate matter air pollution. Four sites were located at streets with heavy traffic and two were control sites in the rural part of the city. The free radical content in each part of the plant was measured by electron paramagnetic resonance. The leaf was selected as the most appropriate part of the plant for the measurement of carbon-derived free radicals. The geff value and the total number of spins were calculated. Relationships were found between location, season, and measurements. The electron paramagnetic resonance spectrum consists of at least two components, which can be attributed to C-type radicals and mixed C + O radicals. Their increase in numbers in the fall seasons, compared to the spring seasons, is also noticeable. It has also been observed that leaves collected in autumn have a higher geff value, which is probably related to the higher amount of oxygen- and carbon-derived free radicals.